Case report: Complete resection of invasive thymoma invading the superior vena cava and right atrium under cardiopulmonary bypass support - Zhang, Xiangxin; Chen, Liang; Zhou, Wenyong; Wang, Zhexin; Wang, Chong; Shi, Jianxin; Yao, Feng (Frontiers in Oncology, 2022)
Here we describe an uncommon case of a 48-year-old male patient with an invasive thymoma invading the superior vena cava, the bilateral innominate veins, right internal jugular vein, right subclavian vein, right atrium, azygos vein and part of lung tissues. The tumor was completely resected under cardiopulmonary bypass support, and the venous bypass using a vascular graft was successfully established between the left innominate vein and right atrium. The postoperative course was uneventful, and the patient was discharged 15 days after surgery without any complications.